1997
DOI: 10.5980/jpnjurol1989.88.434
|View full text |Cite
|
Sign up to set email alerts
|

Stone Recurence After Stone Free Status With Extracorporeal Shock Wave Lithotripsy

Abstract: This results suggested that the stone number, stone history and urological complication were highly related to ipsilateral stone recurrence after stone free status by ESWL. Extracorporeal shock was lithotripsy had probability of higher stone recurrence rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
1
7
2
2
Order By: Relevance
“…These results were found to be similar with many studies previously done, but not with the others [4,5,15]. For current study and generally, it is reasonable that stone burden might influence probability of remaining residual fragments, or might be a reflection of etiologic factors such as urinary tract infection or metabolic abnormalities causing higher recurrence rate.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These results were found to be similar with many studies previously done, but not with the others [4,5,15]. For current study and generally, it is reasonable that stone burden might influence probability of remaining residual fragments, or might be a reflection of etiologic factors such as urinary tract infection or metabolic abnormalities causing higher recurrence rate.…”
Section: Discussionsupporting
confidence: 87%
“…Iguchi et al [12], in their experimental study, discovered that female sex hormones could inhibit renal crystal deposition in rats. However there are also studies claiming ineffectiveness of sex on stone recurrence like our study [3,5,10,13]. In addition the fact that the male to female ratio was almost equal in our study might reflect the higher incidence of infection stones in females.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In our present study, the recurrence rates at 1, 5 and 10 years after ESWL were 0.8%, 35.8% and 60.1% using KaplanMeier analyses. Other studies have also calculated cumulative recurrence rates using the Kaplan-Meier method [17,18]. In one study [17], the overall ipsilateral recurrence rates were 3.5%, 21.2%, 34.7% after 1, 3 and 5 years, respectively; and the contralateral stone recurrence rates were 1.9%, 7.5%, 12.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During the recent 5 years a series of studies [29, 30, 31, 32]reported recurrences after ESWL. Recurrence rates and stone frequencies are given in table 5c.…”
Section: Prospective Studiesmentioning
confidence: 99%